Pengaruh Sosialisasi Pajak, Kesadaran Wajib Pajak Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Dalam Membayar Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan (PBB-P2) Di Kecamatan Cicurug Kabupaten Sukabumi - Rizky Pebriansyah; Susy Hambani; Yoyok P.Hutomo (AKUNTANSI 45, 2024)
Land and build tax is one of the sources of revenue. Taxpayer compliance in paying land and building tax can make it easier for local governments to carry out regional development. But in reality, not all taxpayers fulfill tax obligations. there are still many people who don’t pay and report taxes, this hinders the government in obtaining state revenue from the taxation sector and also hampers regional development.This study aims to determine the effect of tax socialization, taxpayer awareness, and tax sanctions on taxpayer compliance in paying land and building tax rural and urban sector (PBB-P2) in cicurug district, sukabumi regions. The population in this study were all PBB-P2 taxpayers in Nanggerang village, cicurug district, sukabumi regoins consisting of 2.521 taxpayers. In withdrawing the sample, purposive sampling method was used. Based on slovin formula, the number of samples or respondents in this study was 100 taxpayers of PBB-P2 with sampling techniques classified into probability sampling with proportional sampling. the result showed that simultaneously tax socialization, taxpayer awareness, and tax sanctions have a positive effect on compliance of taxpayers of PBB-P2. Partially tax socialization has no effect on on compliance of taxpayers of PBB-P2, while taxpayer awareness and tax sanctions have a positive effect on compliance of taxpayers of PBB-P2.